1992
DOI: 10.1159/000247462
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cellular Retinoic Acid-Binding Protein Type II (CRABP-II) and Down-Regulation of CRABP-I in Psoriatic Skin

Abstract: Cellular retinoic acid-binding proteins (CRABPs) might exert a physiological function by controlling the intracellular levels of free retinoic acid. The aim of this study was to analyze the relative expression of CRABP-I and CRABP-II in lesional (LPS) and nonlesional (NLPS) psoriatic skin. CRABP-I and -II proteins were analyzed by a PAGE-autoradioblotting technique, and their respective mRNA were studied by RNA blot and in situ hybridization. We found that CRABP-II levels were 6-fold higher in LPS and 2-fold i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Third, squamous cell carcinomas frequently display reduced RARγ expression [21,22], and the RAR and RXR levels are progressively suppressed during malignant transformation of human epidermis [10]. Fourth, studies of psoriatic epidermis, characterized by abnormal differentiation and hyperproliferation, have disclosed reduced mRNA expression of RARα and RXRα [23] and increased expression of CRABPII [24,25] that fails to respond to RA treatment [25]. Nonetheless, RArelated drugs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Third, squamous cell carcinomas frequently display reduced RARγ expression [21,22], and the RAR and RXR levels are progressively suppressed during malignant transformation of human epidermis [10]. Fourth, studies of psoriatic epidermis, characterized by abnormal differentiation and hyperproliferation, have disclosed reduced mRNA expression of RARα and RXRα [23] and increased expression of CRABPII [24,25] that fails to respond to RA treatment [25]. Nonetheless, RArelated drugs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A number of gene products have been described whose expression is altered in psoriasis. Among these are the low molecular weight proteins cellular retinoic acid-binding protein type II (CRABP II) and psoriasin [1][2][3]. CRABP II is an intracellular protein which binds retinoic acid and may serve to regulate cellular retinoic acid concentrations and thus the effects of retinoic acid on differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that CRABP-I and -II arc expressed in normal skin to approximately the same extent. However, in abnormal skin differentiation, the level of CRABP-II strongly increases while that of CRABP-I decreases below the threshold of detection [ 19], In submerged keratinoevte cultures, where cells stratify and differentiate without reaching terminal differentia tion states such as skin, CRABP-II levels were increased only in differentiating cells, whereas CRABP-II was unde tectable in nondifferentiated cells (basal layer) [20]. CRABP-I was never detected in the various in vitro sys tems analyzed [21].…”
Section: Intracellular Transport: Cytosolic Retinoid-binding Proteinsmentioning
confidence: 94%